Fecal bacteria-free filtrate transplantation is proved as an effective way for the recovery of radiation-induced individuals in mice - Zhang, Hang; Dong, Miaomiao; Zheng, Jixia; Yang, Yapeng; He, Jinhui; Liu, Tianhao; Wei, Hong (Frontiers in Cellular and Infection Microbiology, 2024)
Background Ionizing radiation can cause intestinal microecological dysbiosis, resulting in changes in the composition and function of gut microbiota. Altered gut microbiota is closely related to the development and progression of radiation-induced intestinal damage. Although microbiota-oriented therapeutic options such as fecal microbiota transplantation (FMT) have shown some efficacy in treating radiation toxicity, safety concerns endure. Therefore, fecal bacteria-free filtrate transplantation (FFT), which has the potential to become a possible alternative therapy, is well worth investigating. Herein, we performed FFT in a mouse model of radiation exposure and monitored its effects on radiation damage phenotypes, gut microbiota, and metabolomic profiles to assess the effectiveness of FFT as an alternative therapy to FMT safety concerns. Results FFT treatment conferred radioprotection against radiation-induced toxicity, representing as better intestinal integrity, robust proinflammatory and anti-inflammatory cytokines homeostasis, and accompanied by significant shifts in gut microbiome. The bacterial compartment of recipients following FFT was characterized by an enrichment of radioprotective microorganisms (members of family Lachnospiraceae). Furthermore, metabolome data revealed increased levels of microbially generated short-chain fatty acids (SCFAs) in the feces of FFT mice. Conclusions FFT improves radiation-induced intestinal microecological dysbiosis by reshaping intestinal mucosal barrier function, gut microbiota configurations, and host metabolic profiles, highlighting FFT regimen as a promising safe alternative therapy for FMT is effective in the treatment of radiation intestinal injury.